Production of biodiesel from pentaclethra macrophylla seed oil. (8th October 2012) - Oshieke, Kinsgley Chinonyerem; Jauro, Aliyu
In the present work, the potentials of pentaclethra macrophylla (Africa oil bean) seed oil (PMSO) are evaluated for the first time as a feedstock for biodiesel. Methyl (PMFAME) and ethyl (PMFAEE) esters of PMSO were produced by standard transesterification procedure using potassium hydroxide (KOH) as catalyst and their qualities determined. Gas chromatography mass spectrometry (GCMS) runs of the biodiesels revealed that the linoleic acid (unsaturated fatty acid) of the methyl esters (55.68%) and ethyl esters (33.45%) of PMSO dominate the fatty acid profile. The viscosity, flash point, cloud point, pour point and acid number of PMFAME and PMFAEE were found to be 4.08 mm 2 /s and 4.16 mm 2 /s; 196°C and 198°C; –5°C and 2°C; 0°C and 1°C; 0.50 mgKOH/g and 0.20 mgKOH/g. The calculated cetane number of 36.72 and higher heating value of 40.47 KJ/g were obtained for both PMFAME and PMFAEE. These together with other fuel parameters were compared with those of soy oil fatty acid methyl esters (SFAME) and ethyl esters (SFAEE), diesel – fuel (D2 ), ASTM and European (EN 14214) standards. The results obtained indicate that PMSO appears to be a potential feedstock for biodiesel production.